El lobo y las siete cabritas - Grimm, Jacob, 1785-1863.; Percy, Graham; Grimm, Wilhelm, 1786-1859. (Barcelona, Spain : Peralt Montagut Ediciones)
Mother Goat rescues six of her kids after they are swallowed by a wicked wolf.
Cuentos en imagenes.
Based on the book of the same title, illustrated by Graham Percy.
Simplified Spanish translation of Grimm's Wolf und die sieben jungen Geisslein.
In Spanish.500.
Keywords: Fables -- Juvenile fiction; Wolves -- Folklore -- Juvenile fiction; Spanish language -- Texts -- Juvenile fiction; Fairy tales -- Juvenile fiction; Folklore -- Juvenile fiction; Children's stories; Juvenile -- El Dorado County Library